MIDICULOUS SOFTWARE: ONLINE PIANO LEARNING MEDIA SOLUTION IN THE ERA OF SOCIETY 5.0 - Putra, Zakarias Aria Widyatama (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
The development in the era of society 5.0 presents various applications of piano learning media based on digitalization and technology. Midiculous software is a software that can be used as an alternative and solution for piano tutors, teachers, and educators who find it difficult to create a piano learning system in online classes. Problem solving is revealed by descriptive qualitative with the process of data collection based on observation. Followed by the stages of preparing a lattice of interview instruments for the speakers (tutors, teachers, and educators) to be triangulated by experts and analyzed with the stages of collection, reduction, presentation, and conclusion drawing. As a result, midiculous software can be used and utilized by piano tutors, teachers, and educators in terms of understandability and usefulness as an online piano learning media. The students of each piano tutor, teacher, and educator are also clearer in receiving piano materials. However, there is a need for strong connectivity between the used devices, such as OBS and Zoom so that piano learning can also be optimized.